Determinants of Inflation in the Euro Area : The Role of Labor and Product Market Institutions - Morsy, Hanan; Jaumotte, Florence (Washington, D.C. : International Monetary Fund, 2012)
While inflation differentials in a monetary union can be benign, reflecting a catch-up process, or an adjustment mechanism to asymmetric shocks or different business cycles, they may also indicate distortions related to inefficiencies in domestic product and labor markets that amplify or make more persistent the impact of shocks on inflation. The paper examines the determinants of inflation differentials in the euro area, with emphasis on the role of country specific labor and product market institutions. The analysis uses a traditional backward-looking Phillips curve equation and augments it to explore the role of collective bargaining systems, union density, employment protection, and product market regulation. The model is estimated over a panel dataset of 10 euro area countries over the period 1983-2007. Results show that high employment protection, intermediate coordination of collective bargaining, and high union density increase the persistence of inflation. Oil and raw materials price shocks are also more likely to be accommodated by wage increases when the degree of coordination in collective bargaining is intermediate. These results are robust to different estimation methods, model specifications, and outliers. The paper suggests that reforming labor market institutions may improve the functioning of the euro area by reducing the risk of persistent inflation differentials.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet